Conceptual approaches to ensuring financial security of it companies in the context of smart economy and digitalisation - Rumyk, Ihor; Puzyrova, Polina; Румик, Ігор Іванович (Scientific Center of Innovative Researches OÜ, 2025)
The article examines comprehensive approaches to ensuring financial security, which take into account the specifics of digital technologies, economic changes, and also ensure compliance with regulatory requirements that require constant updating of knowledge, introduction of innovative approaches to financial planning and risk management, which is the key to stability and successful functioning of IT companies in the context of the smart economy and digitalisation. The purpose of the article is to study conceptual approaches to ensuring financial security of IT companies in the context of the smart economy and digitalisation, focusing on integrated approaches to managing financial flows and risks in the context of digital business transformation, contributing to the development of methods that allow IT companies to adapt to new economic realities while maintaining their financial stability and competitiveness in the market. It is established that the smart economy and digitalisation not only increase the efficiency of financial management, but also contribute to the resilience of IT companies to external and internal challenges, which ultimately ensures their financial security and sustainable development. It is proved that the financial security of IT companies in the context of the smart economy and digitalisation is a key factor in sustainable development and competitiveness, which includes a set of measures aimed at protecting financial resources, ensuring risk resilience and effective management of financial flows. The article proposes the implementation of an algorithm for ensuring financial security of IT companies in the context of the smart economy and digitalisation, which will help IT companies to ensure financial security, adapt to the challenges of the digital economy and maintain stability in a dynamic market environment. The area for further research is to develop financial security models that take into account the specifics of digital technologies, such as blockchain, artificial intelligence, big data, and process automation.
Keywords: financial security; IT enterprises; smart economy; digitalisation; financial planning; cyber threats; blockchain; artificial intelligence; process automatio